Benzaldehyde, A New Absorption Promoter, Accelerating Absorption on Low Bioavailability Drugs Through Membrane Permeability - Wen, Wen; Luo, Jie; Li, Ping; Huang, Wenge; Wang, Ping; Xu, Shijun (Frontiers in Pharmacology, 2021)
Styrax, one of the most famous folk medicines, is a necessary medicine in formulas to help other drugs reach the focal zone and maximize the effectiveness, the mechanism that promotes absorption is not clear yet. This study was carried out to investigate the absorption-promoting effects and the mechanism of benzaldehyde, a key active compound of styrax, on the diffusion rates of drugs with different oral bioavailability. Caco-2 transport experiments were used to investigate the transport rate. Molecular Dynamics Simulation analysis and fluorescence-anisotropy measurements were used to explore the underlying mechanism of absorption-promoting. Validation test in vivo was carried out to reveal the absorption-promoting effects of benzaldehyde on high hydrophilicity drugs. Our data indicated that benzaldehyde(50μM) elevated the cumulative quantity of passively diffusion drugs with high hydrophilicity such as acyclovir and hydrochlorothiazide. MD and membrane fluidity data explained that benzaldehyde can loosen the structure of the lipid bilayer. The validation tests showed that benzaldehyde(140mg/kg) remarkably increased the Cmax and AUC0-6 of acyclovir and hydrochlorothiazide in vivo. These present studies suggested that benzaldehyde can promote the absorption of drugs with lower oral bioavailability through disturbing the integrity of lipid bilayer enhanced membrane permeability.